Current issue in corporate waqf in Malaysia - Omar, Abdul Jalil (American Scientific Publishers, 2018)
Corporate waqf is still new for the contemporary Islamic studies in Malaysia. There are limited resources and guidance to explain about corporate waqf. The purposes of this study are to explore the issues, concept and development of corporate waqf. Current structure for corporate waqf also being explored as part of case studies. This paper provides several perspectives and suggestions to this issue. The methodology for this study is secondary data approach by using the data analysis from the related journal and paper. The subject for this study is Selangor Muamalat. This paper come out with the concept and development of the contemporary waqf focused on corporate waqf and there are five current issues identified in the contemporary waqf. Next, seven proposed action plans are suggested to cover the issues. Lastly, the structure of Selangor Muamalat is analyses by focusing on the management structure, financial and operational framework and the Shariah consideration towards Selangor Muamalat structure.